De(a)fining consent: Exploring nuances of offering and receiving sexual consent among Deaf and Hard-of-Hearing people - Letico, Vanessa (Criminology & criminal justice, 2025)
Deaf and Hard-of-Hearing persons may rely upon non-verbal modes of communication to convey and attain sexual consent. However, this may increase the risk of inaccurate interpretation, sexual miscommunication and potentially, harm. Through an analysis of four online Reddit and Quora discussion threads, this article examines how sexual communication is being negotiated and adapted where at least one party is Deaf or Hard-of-Hearing to better ensure free and voluntary consent. This article offers insights into how sign, touch, lipreading, sound, light and body movement can be expressed as mutually understood cues in clarifying and communicating sexual consent. The importance of clearly understood consent before and during sexual intimacy is increasingly relevant for respectful relationships, education policies and legal frameworks.